“I think the arts are as prominent as any subject”: A study of arts education in two Scandinavian schools - Christophersen, Catharina; Ferm Thorgersen, Cecilia (Nordic Journal of Art & Research, 2015)
The arts seem to be under pressure in many educational systems, which is demonstrated by a general lack of recognition of aesthetic experience and learning, a lack of emphasis on the arts in education, and often also a lack of fully competent teachers. Despite the challenging situation facing the arts in schools in general, there are exceptions. Some schools do choose to focus on the arts. This article is based on an ethnographic double case study that explored arts education practices in two such Scandinavian schools. The purpose was to examine how education in the arts subjects was carried out in the schools, and how the actors perceived, articulated and legitimated the educational practices in the arts subjects. The case descriptions of the two schools imply that the educational leadership in the schools were of great importance. Further, that the arts are integrated as a natural part of everyday school life, and both schools have taken a holistic approach to education, in which the arts are perceived to involve and contribute to learning in the broadest sense, as well as to the pupils’ social and personal growth. Also, the case descriptions show that arts education practices were carried out in a creative, but challenging tension between frames and freedom.